Taxonomic review of catsharks of the Scyliorhinus haeckelii group, with the description of a new species (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) - Soares, Karla D. A.; Gomes, Ulisses L.; Carvalho, Marcelo R. De (Zootaxa, 2016)
Sharks of the genus Scyliorhinus from the southwestern Atlantic are reviewed; identification problems and taxonomic misinformation given in the literature are rectified. After extensive examination of the external and internal morphology of specimens collected mostly off southeastern and southern Brazil, Scyliorhinus besnardi Springer & Sadowsky, 1970 is placed in the synonymy of S. haeckelii (Miranda Ribeiro, 1907), which is thoroughly redescribed. Additionally, a new species, Scyliorhinus cabofriensis, sp. nov., is described from the state of Rio de Janeiro, distinguished from all southwestern Atlantic congeners by its color pattern, clasper and neurocranial morphology, and proportional measurements. A key to Scyliorhinus species occurring in the southwestern Atlantic is also provided.